Assess of isokinetic trunk strength in elite basketball players - Lopez-Illescas, A.; Perez Toledano, J. J.; de Campos Gutierrez de Calderon, A.; Caraca Valente, J. P. (Archivos de medicina del deporte, 2008)
Basketball is a sport discipline which requires strength, speed and endurance. Players` huge size and weight determine a high level of trunk muscle strength. The assess of trunk strength and of the abdominal strength/ back strength ratio are main elements when analysing the ef ficiency of training, as well as its probable impairments. Objectives: - Find out which tests and parameters are the most suitable and discriminative to assess isokinetic trunk strength in basketball players. - State reference values regarding isokinetic strength in elite basketball pla- yers. - Establish elements to improve training and performance qualities. Materials and methods: Subjects: 32 healthy basketball players (age range, 18 - 28 years) Control group: 60 non sport practising students (age range, 18 - 26 years) Instruments and protocol: System ISOKINETIC BIODEX SYSTEM3 Dual position Back Ex/ Flex. The following protocol was followed: - Clinical evaluation of the spinal column. - Teleradiology (Anteroposterior and Lateral) of the spine - Isokinetic trunk tests: Each test was performed in two different positions: Semi-Standing (Functional) and Seated Compressed (Analytical). - 1st test: Flexion / Extension. ROM 90º, velocity 60º/s (10 repetitions). - 2nd test: Flexion / Extension. ROM 90º, velocity 90º/s (10 repetitions). - 3rd test: Flexion / Extension. ROM 90º, velocity 120º/s (20 repetitions). Analysed data: Morphology of the curve, Maximum Peak Torque (N•m), Total Work (Joules), agonistic/antagonistic ratio, and Angle distribution of peak torques along the Range of Movement. Results: - Basketball players showed higher values of Maximum Peak Torque and Total Work than those found within the control group. - Basketball players results didn ?t show significative differences regarding agonistic / antagonistic ratio, when compared with data found within the control group. - Angle of maximum peak torque values were not conclusive, for great data dispersion appeared within data analysis. - The most discriminative parameter was Total Work The numerical values will be shown within tables and graphs. Conclusions: - Isokinetic testing is a valid and reliable method to assess trunk strength in elite basketball players. - The study of muscular balance regarding agonistic / antagonistic ratio over healthy basketball players has shown useful to improve the sport gesture technique within play, therefore stabilising the position of the back. - Further study is essential for a suitable evaluation of the morphology of the isokinetic curve.